The Development of Autobiographical Memory, Autobiographical Narratives, and Autobiographical Consciousness. Issue 1 (February 2020) - Nelson, Katherine; Fivush, Robyn
In this article, we expand on aspects of autobiographical memory initially laid out in our earlier exposition of the sociocultural developmental model. We present a developmental account of the integration of an extended subjective perspective within an extended narrative framework both of which are mediated through language and shared cultural narratives that culminate in autobiographical consciousness . Autobiographical consciousness goes beyond simple memories of past events to create a sense of extended self through time that has experienced and reflexively evaluated events. We argue from philosophical, evolutionary, and developmental psychological perspectives that narratives are a critical form of human consciousness, and that this form is learned through everyday social interactions that are linguistically mediated. Language has "double-duality" in that it is both outward facing, allowing more explicit, organized and differentiated communication to and with others, and language is also inward facing, in that language provides tools for organizing and differentiating internal consciousness. Although consciousness itself is multifaceted, we argue that language is the mechanism without which this particular form of human autobiographical consciousness would not develop.